ADAPTAÇÃO TRANSCULTURAL E VALIDAÇÃO DO “CARE ABILITY INVENTORY”: INVENTÁRIO DE HABILIDADE DE CUIDADO - Rosanelli, Cleci L. S. P.; Gutiérrez, Maria G. d. R.; Beuter, Margrid (Salão do Conhecimento, 2013)
Resumo